Decreased smooth muscle component in Müller's muscle may induce or aggravate blepharoptosis in elderly Asians. (December 2020) - Zhang, Minchen; Zhou, Rong; Gao, Weicheng
Abstract: Previous studies have suggested that the senile ptosis is mostly aponeurotic ptosis. Aponeurotic ptosis, the most common cause of acquired ptosis in elderly adults, results from disinsertion or dehiscence of the levator aponeurosis from the tarsal plate. Müller's Muscle is located below the levator aponeurosis, and its main function is to contribute to a few millimeter in upper eyelid elevation. In recent years, studies have shown that Müller's Muscle plays a more important role in the eye-opening process than previously reported. There are few reports on the changes of smooth muscle component with age in Müller's Muscle. As far as we know, it has not been written up previously. Through histological study on Müller's Muscle of Chinese cadaver specimens, we found that Müller's Muscle contained obvious smooth muscle components above the upper edge of the tarsus in the specimen of a child. However, in elderly specimens, we observed that the smooth muscle components decreased gradually even faded away from originated inferior branch of levator superioris muscle to upper margin of tarsus. We hypothesized that the number of smooth muscle components in Müller's Muscle gradually decreases, with the increase of age, which further affects the function of Müller's Muscle in assisting levator muscle, and further causes or aggravates ptosis. Our hypothesis needs to be further verified by more autopsy histological studies of different ages and genders, so as to provide a new idea for the clinical diagnosis and treatment of ptosis.